2003
DOI: 10.1177/1099636203005001584
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanisms and Modelling of Impact Damage in Sandwich Beams - A 2D Approach: Part I - Experimental Investigation

Abstract: This paper addresses the effect of low velocity impact damage on postimpact failure mechanisms and structural integrity of foam core sandwich beams subjected to edgewise compression, shear and bending load cases. The study deals with a 2D configuration, where a sandwich beam is impacted by a steel cylinder across the whole width of the specimen. The impact damage is characterised as indentation of the core with sub-interface damage seen as a cavity while the GFRP faces remain virtually unaffected by the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 13 publications
1
72
0
Order By: Relevance
“…Since the foam is crushed and has significantly reduced strength, and in some cases there is even a cavity underneath the face, shear loading is relevant, just as for an interface crack. This case was experimentally investigated in [22] and modelled in [23] for a configuration with a core cavity. The experimental set-up used a four-point bending configuration, as depicted in Fig.4, with the impact damage located between an inner and outer support, i.e., in the shear zone.…”
Section: Impact Damage In Sandwich Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the foam is crushed and has significantly reduced strength, and in some cases there is even a cavity underneath the face, shear loading is relevant, just as for an interface crack. This case was experimentally investigated in [22] and modelled in [23] for a configuration with a core cavity. The experimental set-up used a four-point bending configuration, as depicted in Fig.4, with the impact damage located between an inner and outer support, i.e., in the shear zone.…”
Section: Impact Damage In Sandwich Beamsmentioning
confidence: 99%
“…The residual strength prediction models of foam core sandwich beams with impact damage used in [21][22][23][24] are all based on detailed descriptions of the crushed core zone, both in terms of geometry and the properties of the crushed core material. The crushed core properties were obtained from experiments where the core was pre-crushed in compression, allowed to relax and then tested in tension, compression and shear in various directions [22]. It was found that the as-crushed moduli and strengths dropped significantly compared to non-crushed foam and that the crushed foam became highly orthotropic.…”
Section: Impact Damage In Sandwich Beamsmentioning
confidence: 99%
“…Conrad and Sayir (1998) capture the dynamic failure process of a foam sandwich subjected to a foreign object impact using a high speed camera, from which the failure mechanism involved in the impact event, i.e., core shear failure, debonding between the face sheets and core material, and face sheet tensile failure, is clearly depicted. Shipsha et al (2003) study failure mechanism and modeling of impact damage in sandwich beams through an experimental investigation, and the different failure modes involved are characterized. Lim et al (2004) study failure modes of foam core sandwich beams under static and impact loads.…”
Section: Impact Damage In Composite and Sandwich Structuresmentioning
confidence: 99%
“…The core was sandwiched between two face sheet carbon fiber laminates with thickness of 1.52 mm. The face sheets were produced from T700 unidirectional textile with an areal density of 192 g/m 2 Yan Li, An Xuefeng, and Yi Xiaosu chosen. Sandwich composite panels were manufactured by resin transfer molding (RTM) process.…”
Section: Experimental Studymentioning
confidence: 99%
“…A frequent cause of such damage is in-service incidents (runway debris, careless handling, etc.) or interactions with attached structures (pillars, bends, etc) [2][3][4]. It should be noted that such damages of sandwich composites usually cannot be observed outside.…”
Section: Introductionmentioning
confidence: 99%